Consumer Perception of Conversational Commerce from the Perspective of Bangladesh (Dhaka University Journal of Business Studies, 2026)
The use of Conversational Commerce tools (AI-powered chatbots, messaging apps, voice assistants, and live chats) is getting popular gradually across the world to attract more customers online. The study focuses on studying the appliances of conversational commerce and their underlying impact on consumers’ perception of accepting and adopting conversational commerce from the perspective of Bangladesh. The study used the Technology Acceptance Model (TAM) 3 to determine the variables that influence consumers’ perceptions. A questionnaire was formed based on the 14 variables of TAM and distributed to gather data from 106 Bangladeshi web users using a multistage sampling method. The study analyzed the collected data based on the Confirmatory Factor Analysis (CFA) model using AMOS and SPSS V29. The paper outlines that the adoption and acceptance of conversational commerce mainly depend on consumers’ behavioral perceptions. And the behavioral intention that influences consumers buying decisions is significantly impacted by the perceived usefulness of conversational commerce. Furthermore, the perceived effectiveness of conversational commerce is affected mainly by consumers’ perceived ease of use. Moreover, the article highlights promising growth in the acceptance of C-commerce as around 85.5% of the respondents preferred to interact with brands by using messaging applications. The paper also identified customer service as the most vital point of satisfaction, yet the emerging realm of conversational commerce is replete with difficulties that manifest mainly in the form of discontentment of Bangladeshi consumers through lack of consultation and additional trouble during purchases.Journal of Business Studies, Vol. XLIV, No. 1, 2025 Page 53-76